The value of enzyme preparation added to cattle rations - Richardson, D.; Koch, B.A.; Smith, E.F.; Ward, J.K.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Three lots of 10 heifer calves each were fed the same ration except for the added enzyme preparations. Ingredients and average daily consumption are show in Table 19. Lot 1 served as the control. The enzyme preparations were added to the soybean oil meal at the following rates per ton: Lot 2, 2.5lbs. amylase (acts on carbohydrates); Lot 3, 2.5lbs. amylase plus 6 lbs. protease (acts on proteins). Rumen samples were obtained to determine the concentration of volatile fatty acids and percentage distribution of acetic, propionic, and butyric acids in the rumen fluid.
Keywords: Beef; Enzyme; Soybean oil meal; Gain